2013
DOI: 10.1155/2013/931972
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib in Advanced Hepatocellular Carcinoma: A Nationwide Retrospective Study of Efficacy and Tolerability

Abstract: Background. Advanced HCC is a clinical challenge with limited treatment options. The multikinase inhibitor sorafenib is the first and only agent showing a survival benefit in these patients. In this study we evaluate the efficacy and tolerability of sorafenib in an unselected patient population. Furthermore we explore the role of alpha-fetoprotein (αFP) as a potential biomarker for treatment efficacy and correlation to survival. Methods. Seventy-six patients with advanced HCC, not eligible for locoregional the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 15 publications
6
26
0
Order By: Relevance
“…These findings have not been clearly shown in randomized studies but have been demonstrated in some retrospective studies. In a retrospective study, Køstner AH et al found the median OS as 6.2 months in patients with an ECOG performance status of 0-1, and 1.8 months in those with a PS of 2-3 (Køstner et al, 2013). OS was 67 weeks in patients with PS 0 in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…These findings have not been clearly shown in randomized studies but have been demonstrated in some retrospective studies. In a retrospective study, Køstner AH et al found the median OS as 6.2 months in patients with an ECOG performance status of 0-1, and 1.8 months in those with a PS of 2-3 (Køstner et al, 2013). OS was 67 weeks in patients with PS 0 in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…22 patients on sorafenib had BCLC stage C, with only 1 patient being in BCLC stage B. We observed a median OS of 3 months in patients on sorafenib whereas patients on best supportive care had median OS of 2 months, which is similar to outcomes reported by Kostner et al 23 Lee et al too report a poor median OS of 4 months and similar toxicity profile of advanced HCC patients on sorafenib.…”
Section: Tumor Characteristicssupporting
confidence: 88%
“…21,22 Kostner et al in their retrospective study of sorafenib in HCC, noted median OS of only 1.8 months of patients in PS 2-3. 23 In our study, 66% of our patients had PS≥2. 22 patients on sorafenib had BCLC stage C, with only 1 patient being in BCLC stage B.…”
Section: Tumor Characteristicssupporting
confidence: 46%
“…Small series reported the value of baseline and changes in AFP plasma levels to predict response and outcome for patients with advanced HCC treated with sorafenib. Several studies showed consistent correlation between early (varying from 2 to 8 wk) decrease of AFP level more than 20% following sorafenib and objective response [69][70][71][72][73] and better outcome [69][70][71]73] in patients with advanced HCC. Personeni et al [71] showed that early responders, defined by a 20% decrease of AFP 8 wk after sorafenib treatment, had significantly better median OS and TTP compared to non-responders (13.8 mo vs 8.2 mo, P = 0.022 and 7.9 mo vs 2.4 mo, P = 0.004; respectively) [71] .…”
Section: Poorer Prognosismentioning
confidence: 84%
“…Køstner et al [72] 76 Retrospective Sorafenib AFP response (> 20% decrease from baseline within the first four weeks)…”
Section: Poorer Dfs Higher Vascular Invasionmentioning
confidence: 99%